PENINGKATAN KENYAMANAN TERMAL TAMAN KOTA MELALUI MODEL TAMAN AIR BERARSITEKTUR TRADISONAL BALI - I WAYAN WIRYA SASTRAWAN; I GEDE SURYA DARMAWAN (Universitas Mahasaraswati K. Mataram, 2024)
Thermal comfort is a crucial aspect in designing outdoor spaces such as urban parks. Traditional Balinese water gardens have the potential to enhance thermal comfort through the application of water elements and traditional architectural concepts. Previous research by Wirya et al. (2017) identified three models of traditional Balinese water gardens with optimal thermal comfort levels. However, the application of these models in modern urban parks has not been extensively studied. This research aims to develop an optimal urban park design concept in terms of thermal comfort by applying traditional Balinese water garden models. The method used is experimental, employing simulation techniques using Envi-met software. The research objects are three urban parks in Bali: Taman Kota Alit in Tabanan Regency, Lapangan Astina in Gianyar Regency, and Lapangan Kapten Mudita in Bangli Regency. The results show that the application of traditional Balinese water garden models can improve thermal comfort in urban parks. The distribution patterns of air temperature and humidity are more evenly spread with the presence of water elements and vegetation arranged according to traditional Balinese concepts. Wind speed is also better controlled, creating a more comfortable microclimate. The resulting design concept can serve as a recommendation for designing urban parks that are optimal in terms of thermal comfort while maintaining local architectural values.